АНТР ОПОЛОГІ ЧНІ ВИМІР И ДУХОВНОСТІ В КОНТЕ КСТІ РОЗВИТКУ ФІЛ ОСОФСЬКО-ПЕ ДАГОГІ ЧНОЇ ДУМКИ - Oleksyuk, O (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the problem of finding the anthropological foundations of spiritual personality in art education. Analyzes the historical sequence of ideas about spirituality in personality philosophical and pedagogical concepts.